The influence of disturbance scale on the natural recovery of biological soil crusts on the Colorado Plateau - Jech, Sierra D.; Havrilla, Caroline A.; Barger, Nichole N. (Frontiers in Microbiology, 2023)
Up to 35% of global drylands have experienced degradation due to anthropogenic impacts including physical disturbances like trampling and soil removal. These physical disturbances can result in the loss of soil communities known as biological soil crusts (biocrusts) and the important functions they provide, such as soil stability and fertility. The reestablishment of biocrust organisms after disturbance is determined by many factors including propagule availability, climate, and vascular plant community structure. The role of these factors in natural recovery may be intensified by the extent (or size) of a disturbance. For example, large disturbances can result in reduced propagule availability or enhanced erosion which impact both the dispersal and establishment of biocrust organisms on disturbed soils, leading to slower natural recovery. To test how disturbance extent impacts biocrust natural recovery, we installed four disturbance extents by completely removing biocrust from the mineral soil in plots ranging from 0.01 m2 to 1 m2 and measured productivity and erosion resistance. We found that small disturbance extents did not differ in chlorophyll a content, total exopolysaccharide content, or soil stability after 1.5 years of natural recovery. However, the concentration of glycocalyx exopolysaccharide was higher in the smallest disturbances after the recovery period. Our results indicate that disturbances less than one square meter in scale recover at similar rates with soil stability returning to high levels in just a few years after severe disturbance. Our findings align with prior work on biocrust natural recovery in drylands and highlight the opportunity for future work to address 1) cyanobacteria, moss, and lichen propagule dispersal, 2) rates and mechanisms of biocrust succession, and 3) the role of wind or water in determining biocrust colonization patterns as compared to lateral growth.